THE USE OF PROCESS-PRODUCT HYBRID APPROACH TO IMPROVE STUDENTS WRITING SKILLS - Yayan Suryana; Deden Iskandar (Universitas Kuningan, 2015)
This paper comes out of concerns about teaching English writing to vocational high school students in EFL learners context. This study points out how the process-product hybrid approach affects students writing skills in solving some complex problems in order to generate deep comprehension of writing. In this study, quasi-experimental research was applied to measure the students writing improvement by collecting the data from instruments which covered pre-test, post-test, and questionnaire. The findings showed that students writing skill improved significantly. It also revealed that almost all of the students responded the statements positively and they believed that this approach can help them in improving their writing skill since it gives full comprehension of writing and serves more interesting teaching learning activities. Therefore, this integrated approach has become the most recommended approach for teachers to improve students writing competences.